2021
DOI: 10.1088/2515-7639/ac24ec
|View full text |Cite
|
Sign up to set email alerts
|

Neutron studies of Na-ion battery materials

Abstract: The relative vast abundance and more equitable global distribution of terrestrial sodium makes sodium-ion batteries (NIBs) potentially cheaper and more sustainable alternatives to commercial lithium-ion batteries (LIBs). However, the practical capacities and cycle lives of NIBs at present do not match those of LIBs and have therefore hindered their progress to commercialisation. The present drawback of NIB technology stems largely from the electrode materials and their associated Na+ ion storage mechanisms. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…For example, hazelnut shell derived HC in 1 M NaPF 6 in EC : PC (1 : 1) showed capacity fading after the 50 th cycle due to low reversibility of Na + ion storage for HC particles with highest impurities and highest amorphous carbon structure [73] . Half‐cell studies, which are common in LIBs research have been initially adapted for SIBs employing HC anodes and Na metal cathodes [61,74] . However, it has been reported that for HC with Na metal lower rate capabilities have been obtained compared to full‐cell studies [60,69] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hazelnut shell derived HC in 1 M NaPF 6 in EC : PC (1 : 1) showed capacity fading after the 50 th cycle due to low reversibility of Na + ion storage for HC particles with highest impurities and highest amorphous carbon structure [73] . Half‐cell studies, which are common in LIBs research have been initially adapted for SIBs employing HC anodes and Na metal cathodes [61,74] . However, it has been reported that for HC with Na metal lower rate capabilities have been obtained compared to full‐cell studies [60,69] .…”
Section: Resultsmentioning
confidence: 99%
“…[73] Half-cell studies, which are common in LIBs research have been initially adapted for SIBs employing HC anodes and Na metal cathodes. [61,74] However, it has been reported that for HC with Na metal lower rate capabilities have been obtained compared to full-cell studies. [60,69] Hence, our half-cell studies data are in line with half-cell studies reported in the literature.…”
Section: Morphological and Structural Characterization Of The Sprayco...mentioning
confidence: 99%
“…These unique characteristics provide neutrons with distinct advantages for battery studies, offering complementary information to X-ray studies. Due to its high sensitivity to light elements, especially Li, Na, and O, the neutron technology is able to distinguish them from other heavy elements, such as Ni, Mn, and Fe, which are common elements in SIB cathode materials [46].…”
Section: Brief Overview Of Neutron Technologymentioning
confidence: 99%
“…These unique characteristics provide neutrons with distinct advantages for battery studies, offering complementary information to X-ray studies. Due to its high sensitivity to light elements, especially Li, Na, and O, the neutron technology is able to distinguish them from other heavy elements, such as Ni, Mn, and Fe, which are common elements in SIB cathode materials [46]. Some typical neutron scattering technologies are suitable for battery research including neutron diffraction (ND), small-angle neutron scattering (SANS), neutron total scattering combined with pair distribution function (PDF), inelastic neutron scattering (INS), quasielastic neutron scattering (QENS), and neutron imaging [46][47][48][49].…”
Section: Brief Overview Of Neutron Technologymentioning
confidence: 99%
“…The QENS method is a direct method for studying ion dynamics using neutrons [88,89]. As represented in Figure 14, an incident neutron with an initial wavevector of k i interacts with the sample's atomic nucleus and scatters at a 2θ, resulting in a wavevector k f .…”
Section: Second-quasi-elastic Neutron Scattering (Qens)mentioning
confidence: 99%